Lohans’ Magic Squares and the Gaussian Elimination Method - Miranda, Lohans de Oliveira; Miranda, Lossian Barbosa Bacelar (Journal of Nepal Mathematical Society, 2020)
We have established a new general method to build doubly even magic squares. New types of magic squares are built. The method is aesthetic and easy to understand.